Diplomasi Publik Korea Selatan sebagai Kekuatan Menengah di Bawah Kepresidenan Moon Jae In - Tasha Regina Adriana (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2018)
In 2016, the people of South Korea jointly voiced their anger after the corruption committed by Park Geun-Hye and her aide was revealed. National Assembly then voted to impeach Park Geun-Hye, resulting her departure from her post on March 10, 2017. Subsequently, Moon Jae-In succeeded her position as president in May 2017. A year in the office, his administration saw how the scandal that involved the previous president could bring an adverse impact on South Korea's image and as well as jeopardize its position as a middle power. Under the presidency of Moon Jae-In, South Korea moves to use soft power and public diplomacy as a strategy to restore its image. This paper will discuss the strategy of Moon Jae-In’s administration in using both soft power and public diplomacy to maintain its position as a middle power. Public diplomacy approach will be used to analyze how Moon Jae-In strategizes. At the end of the writing, there will be conclusions that discuss how the strategy has gradually brought an impact on South Korea in the eyes of the world.